Earnings surprises, asymmetry of returns and market level changes: An industry study - HO, Yew-Kee (Institutional Knowledge at Singapore Management University, 2007)
Recent studies that examine the relationship between stock returns and unexpected earnings may be broadly categorized into two main approaches: the firm-specific approach of Skinner and Sloan (2002) and Lopez and Rees (2001), and the market-wide regime shifting behavior of Conrad, Cornell, and Landsman (2002). Although both approaches provide possible explanations for the asymmetric behavior of earnings shocks, no known study has attempted to establish which approach has stronger empirical support. In this paper, using industry sector results, we generally find stronger empirical support for the firm-specific approach as being more representative of stock price behavior.